Jaina Thoughts on Unity Not Being a Number - Jadhav, Dipak (History of Science in South Asia, 2021)
At one time, the Jainas in India and the Greeks in abroad held that unity was not a number. This paper provides an insight for the first time into the thoughts offered by the Jainas as to why unity was not a number for them.